Productivity, Nutrient, and Soil Enzymes Influenced with Conservation Agriculture Practices in Peanut. (1st May 2018) - Jain, N.K.; Jat, R.S.; Meena, H.N.; Chakraborty, K.
Abstract : Core Ideas: Peanut–wheat–Sesbania cropping system recorded the highest peanut–pod equivalent yield. Peanut–wheat–Sesbania/ green gram markedly increased soil enzymatic activities. Bulk density decreased in peanut‐CTW and peanut + pigeonpea crop rotations. Peanut ( Arachis hypogaea L.) is a soil‐C depleting crop under a continuous monocropping system. A study was conducted comprising combinations of tillage practices (zero tillage [ZT] or conventional tillage [CT]), crop rotation (sole peanut, peanut‐wheat [ Triticum aestivum L.], or peanut+pigeonpea [ Cajanus cajan L.]), and green manuring (GM) (green gram [ Vigna radiata L.], sesbania [ Sesbania aculeata Willd.], or wheat straw incorporation [WSI]). Peanut pod yield was found higher in peanut followed by wheat either zero tilled (ZTW) or conventional tilled (CTW), and GM either with sesbania/green gram/WSI. Green manuring in peanut–ZTW and peanut+pigeonpea recorded higher grain yield of wheat (3.11 t ha −1 ) and pigeonpea (1.76 t ha −1 ), respectively. Sesbania GM increased root biomass of peanut, wheat, and pigeonpea in all the systems. Peanut‐pod equivalent yield recorded significantly higher in peanut–ZTW or CTW when included GM with either sesbania or green gram (3.64 t ha −1 ). Found higher accumulation of soil N in peanut–ZTW–sesbania (33.8 kg ha −1 ), P in peanut–CTW (6.4 kg ha −1 ), and S in peanut–CTW (3.7 kg ha −1 ) crop rotations. Activities of urease, β‐glucosidase, acid phosphatase, and alkaline phosphatase were increased in all the crop rotations that included green manuring or WSI over sole peanut. Soil bulk density (0–15 cm depth) was recorded lower in peanut–CTW, however, higher in peanut–ZTW. Peanut followed by ZTW or CTW and green manuring either with sesbania or green gram found more sustainable than sole peanut in terms of peanut‐pod equivalent yield and improved soil enzyme activities.